Introduction to Encountering the Digital in Performance: Deployment | Engagement | Trace. - Chatzichristodoulou, Maria (Contemporary Theatre Review, 2017)
An introduction is presented to the issue of the journal that discusses topics such as the participative culture of headphone theater, the impact of digital technology on theatrical performance, and the social aspects of digital culture.